Semantic model of modern gender identity: texts and contexts - O.A. Pushonkova, (Ukrainian Cultural Studies, 2018)
Revealing of the logic of representations in culture is the basis of the modern visual literacy formation. Doubts about the potential of visual information as a reliable source of authenticity, require inclusion of other modes of reality perception, contextual expansion of the very concept of visuality, and interaction with different discourses. The questions of how the evaluation guides of the modern era change the visual language, how its contexts and texts are formed, and, in particular, how it affects the formation of modern gender identity, are acquiring actuality. The gender issue, being a field of interdisciplinary research, most clearly presents changes in the methods of visualization and modeling of reality, therefore, serves as a representative base of the material. Visual gender images show changes in the deep layers of culture, and gender studies are transformed along with changes in cultural field and capture the very nature of cultural change. The visual representation of femininity and masculinity represented in culture is based on the metaphor of sex, appealing to archetypes, the oldest ideas of men and women. Visual representations of gender in culture show a wide range of identification practices, from artificial and distorted corporeality to the return of the "natural body". In the context of modern studies of gender visual representations, we have to identify their connection with the dynamic changes in the structure of identity (fragmentation, mimicry, drifting) and with changes in the cultural codes of corporeality. It is proved that in the conditions of destruction of representative systems it makes sense to speak not only about the specifics of femininity and masculinity, which by losing self-sufficiency are curtailed in selfie-projects, but also about the general repressed subject of culture which lies in the "scissors" of new formats of discipline power: coercion and temptation. The screen demonstrates perfect “human-thing” with a blurred gender identity (new androgen), which keeps the attention, fixes it on itself as a narcissistic selfie-project that absorbs the views of others around through different techniques. It was found that the formation of gender identity changed the nature of sample imitation (as it was before) and acquired the character of simulation, where evaluative independent attitude towards the world or a narcissistic choice in the context of a hedonistic-oriented culture is possible. This arch for samples remains at the deep level of collective symbols and archetypes, which should become the subject of further developments.
Keywords: visual culture, gender relations, identity, visual representation, narcissism, Panoptikon, Synoptikon